A STUDY OF FACTORS INFLUENCING CUSTOMER LOYALTY TOWARDS B AIR IN NEPAL - Joshi, Ashaya Dhoj; Dowpiset, Kitikorn (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2021)
The purpose of the study is to determine the key aspects that influence the customer loyalty towards B Air, a private airlines in Nepal. Customer Loyalty is a key factor for of any airlines and depends highly on airline service quality in the industry. The conceptual framework has been derived from four other theoretical framework with adjustments. Additionally, this study is connected to linking customer loyalty to profitability as customers are valued as lifeline for any business and hence has been reviewed to propose a conceptual framework for building and sustaining customer loyalty and thus maximize profits. The research was carried out with sample data (n=405) collected from three major airports in Nepal by utilizing self- administered questionnaire to the Nepalese citizens The researcher used convenience and judgment sampling method to select the respondents. After the information was collected from the respondents, the data was analyzed and processed on SPSS program. The result shows that perceived value had the greatest influence on customer loyalty for B Air. In addition, in terms of customer satisfaction, the airline image influences most and is more important than airline tangibles, personnel quality and empathy. The contribution of this paper is to analyze the factors that influence customers' loyalty, and thereby help domestic airlines in Nepal improve their customer loyalty effectively. With this research the airlines industry management can move away from the traditional technique of management can use more appropriate methods to attract and retain customers.